ANTIEPILEPTIC DRUG PRESCRIBING FOR CHILDREN IN ITALY. Issue 1 (14th December 2015) - Putignano, Daria; Clavenna, Antonio; Campi, Rita; Bonati, Maurizio
Abstract : The aim of the study was to evaluate prescription profile of antiepileptic drugs (AEDs) in pediatric population. Prescriptions reimbursed by the National Health System, involving 1, 669, 370 children and adolescents, dispensed between 2003–2012 by the retail pharmacies in the Lombardy Region, were analysed. AEDs classified according to International Anatomic-Therapeutical-Chemical Classification system (ATC subgroup: N03A). Prevalence was defined as the number of patients received at least one AED prescription per 1000 inhabitants and incidence was defined as the number of patients received an AED prescription for the first time (no AED prescriptions in the previous 12 months) per 1000 inhabitants. The first prescription dispensed to incident cases was analyzed. During 2012, 6, 088 children and adolescents (3.6‰ of the population) received at least one AED prescription. The incident cases were 1, 465 (incidence 0.86‰). Prevalence and incidence showed significant differences across time. In 2012 about 96% of incident cases was treated with only one AED and of these approximately 78% was treated with an older, while 22% with a newer AED. Valproic acid was the most used at the first prescription (56.2%), followed by carbamazepine (11.5%) and levetiracetam (9.2%). The use of newer AEDs increased across time (χ2t=23.75 P<0.005): in particular the prescriptions of carbamazepine decreased accross time (CAGR: −5.3%), while those of levetiracetam increased (CAGR: +35.4%). Despite conventional AEDs were still the main treatment for epileptic children, there was a decrease of carbamazepine and an increase of levetiracetam. These findings are consistent with results from drug utilization studies performed in other countries.